Soil organic carbon stabilization is influenced by microbial diversity and temperature - Yun Liang; Eva F. Leifheit; Anika Lehmann; Matthias C. Rillig (Scientific Reports)
Abstract The stabilization of soil organic carbon (SOC) is influenced by soil microbes and environmental factors, particularly temperature, which significantly affects SOC decomposition. This study investigates the effects of temperature (ambient: 25 °C; elevated: 27.5 °C) and soil microbial diversity (low, medium, and high) on the formation of stabilized SOC, focusing on mineral-associated organic carbon (MAOC) and water-stable aggregates, through a 75-day model soil incubation experiment. We measured water-stable aggregates, microbial respiration, and SOC in different fractions. Our results demonstrate that microbial diversity is crucial for SOC mineralization; low diversity resulted in 3.93–6.26% lower total carbon and 8.05–17.32% lower particulate organic carbon (POC) compared to medium and high diversity under the same temperature. While total MAOC was unaffected by temperature and microbial diversity, macroaggregate-occluded MAOC decreased by 8.78%, 38.36% and 9.40% under elevated temperature for low, medium and high diversity, respectively, likely driven by decreased macroaggregate formation. A negative correlation between macroaggregate-occluded POC and microbial respiration (r= -0.37, p < 0.05) suggested microbial decomposition of POC within macroaggregates contributed to respiration, with a portion of the decomposed POC potentially stabilized as microbial-derived MAOC. Notably, soils with medium microbial diversity exhibited the highest levels of both macroaggregate-occluded POC and MAOC at ambient temperature; however, elevated temperature disrupted this stabilization, reducing both POC retention and MAOC accumulation within macroaggregates. These findings underscore the temperature-sensitive interplay between microbial diversity and SOC stabilization, highlighting the need to disentangle microbial pathways governing C dynamics under climate change.